ANALISIS METAKOGNITIF MAHASISWA TERHADAP EMPAT KETERAMPILAN BERBAHASA MELALUI PENDEKATAN STUDENT-CENTERED LEARNING BERBANTUAN AI - Nurhasanah, Een; Astri Asmayanti; Hendra Setiawan; Siti Masitoh; Seli Mauludani; Kurnia Dewi Nurfadilah; Alin Ambarwati (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study analysed the metacognitive awareness of 43 D-3 Mechanical Engineering students towards four language skills (speaking, listening, reading, writing) through the Student-Centered Learning approach assisted by artificial intelligence. In contrast to previous studies that focused on quantitative correlation or test results, this study emphasizes metacognitive reflection and the role of AI as a facilitator. Primary data from exit ticket reflection, interactive quizzes, and monitoring of Brisk Boost activities were analysed qualitatively descriptively using case studies, iterative thematic coding, triangulation of sources and investigators, and member checks. The results showed that students were able to identify strengths (e.g., confidence in group discussions) and weaknesses (nervousness in speaking, weak writing structure). AI facilitates the transformation of general reflection into concrete SMART goals (e.g., 3x/week speaking practice for 5-7 minutes, reading 30 minutes/day with 5 new vocabulary), with 70% target achievement and up to 25% increase in cross-skill interaction. The integration of SCL-AI increases active engagement, intrinsic motivation, and awareness of skill interconnection. The findings contribute to the conceptual framework of metacognition–SCL–AI–SMART, with practical implications for lecturers, students, and vocational curricula.